Milestones in Time: The Value of Landmarks in Retrieving Information from Personal Stores - Morris, Meredith Ringel; Cutrell, Ed; Dumais, Susan; Horvitz, Eric (Proceedings of Interact 2003, 2003)
We describe the design and analysis of timeline visualizations for displaying the results of queries on an index of personal content. The visualization was built on top of a personal search engine that provides a unified index of all the information a user has seen, including web pages, email, and documents. Results of searches are presented with an overview-plus-detail timeline visualization. A summary view shows the distribution of search hits over time, and a detailed view allows for inspection of individual search results. In a user study, we explore the value of extending a basic time view by adding public landmarks (holidays and important news events) and personal landmarks (photos and important calendar events).